(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Nguyen DD, Le TA, Hoang QH, Le QT, Nguyen E. 2022. Two new taxa of Curcuma sect. Ecomata (Zingiberaceae: Zingibereae), from coastal Central Vietnam. Biodiversitas 23: 2512-2519. Curcuma sixsensesensis and Curcuma vinhlinhensis, two new species belonging to subgenus Ecomata from Coastal Central Vietnam, are described and illustrated in the present articles. The C. sixsensesensis easily gets confused with C. newmanii Škorni?k. in compact rhizome; short lateral inflorescence composing of a few bracts; white corolla lobes and lateral staminodes; white labellum with a yellow mid-rid band but readily distinguished in rhomboid lateral staminodes (vs. obovate) with apex acuminated (vs. rounded); labellum 3-lobed (vs. emarginated), a mid-rid band being yellow at apex half, white at the base (vs. yellow throughout); anther crest presented (vs. reduced); oblong (lightly arching) (vs. L- shaped) anther in side view with slender and inward-pointing (vs. stout and outward-facing) spurs. The second one is similar to C. pambrosima Škorni?k. & N. S. Lý in general habit and shape of the spike but differs in reduced ligule ca. 1 (vs. 4-5) mm long; lateral staminodes orange throughout (vs. yellow at apex, white at base), elliptic with round apex (vs. unequally ovate-rhomboid with acute apex); anther spurs elongate into the acute apex, outward-facing (vs. curved inward), ca. 2-3 (vs. ca. 1,5) mm long, anther crest reduced, up to 0.5 mm, 2-lobed (vs. prominent anther crest, ca. 1.5 mm apex round). Data for each described species comprises standard citation of type specimens, description, proposed species epithet etymology, data on ecology and distribution, and short taxonomic notes and morphological comparison of these new species with its allies species, a revised key to species of Curcuma sect. Ecomata in Vietnam is included.